Acceleration of Breaking Buds Dormancy on Apricot Trees by Using Alternatives of Hydrogen Cyanamide (Dormex) and Assessment of Resulting Fruits Quality - Karim Farag; Raed Shehata (Turkish Journal of Agriculture: Food Science and Technology)
The purpose of this research was to determine the effectiveness of alternatives of dormex on apricot budbreak and their effect on apricot fruit quality. Our study was carried out on five-years old “Canino” apricot at Badr district, El Behira Governorate, Egypt, during the two seasons 2022 and 2023, respectively. Twenty-four uniform apricot trees were selected and sprayed to the runoff once on 20 and 25 January during 2022 and 2023, respectively, by following treatments: control, mineral oil at 2%, low pyrite urea at 2%, ammonium nitrate at 1.5%, potassium nitrate at 2%, mineral oil combined with low pyrite urea at the same concentration of 2%, mineral oil at 2 % combined with ammonium nitrate at 1.5 %, mineral oil combined with potassium nitrate at the same concentration of 2%. For each of the treatments that were used, 0.05% (v/v) of the non-ionic surfactant tween 80 was applied. In both seasons, the use alternatives dormex chemicals resulted in better budbreak than control trees especially the formulation of mineral oil at (2%) plus potassium nitrate (2%).